Methods of Murder : Beccarian Introspection and Lombrosian Vivisection in Italian Crime Fiction - Past, Elena, 1976- (Book collections on Project MUSE., 2012)
Past traces the roots of the twentieth-century literature and cinema of crime to two much earlier, diverging interpretations of the criminal: the bodiless figure of Cesare Beccaria's Enlightenment-era On Crimes and Punishments, and the biological offender of Cesare Lombroso's positivist Criminal Man.